Analisis Risiko Terhadap Keputusan Pembayaran Menggunakan Metode Shopee Paylater pada Kalangan Mahasiswa di Universitas Muhammadiyah Surakarta - Amelia Fatimah Az Zahra; Shinta Permata Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Technological developments have become increasingly sophisticated, where most activities already use digital technology. Including in transactions and payment methods that already utilize this technology. Shopeepaylater is one of the current payment methods that is carried out after purchase, or known as